Pengembangan Buku Panduan Praktik Pembuatan Alat Permainan Edukatif Sederhana Untuk Optimalisasi Perkembangan Bahasa Anak - Nasution, Raisah; Novita, Nanda; Amelia, Nurul (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
The use of Educational Game Tools helps teachers in stimulating children's language development. However, teachers experience obstacles in making simple APE and lack of guidance in making and applying it. So this study aims to; develop a practical guidebook for making simple APE in language development, test the feasibility of the guidebook product, Test the effectiveness of the guidebook product. This study uses the Research and Development research method. The subjects of this study were 7 PAUD teachers. The guidebook developed is a book that explains the theory related to APE, how to make APE, and steps for implementing the use of APE to optimize children's language development. Based on the results of the feasibility test obtained from the PAUD material expert validator of 85.93%, which is a very feasible criterion and while the results of the assessment of the PAUD teaching material media expert validator obtained a percentage of 86.53%, which is a very feasible criterion. Based on the results of the practicality test, an average of 88.39% was obtained, so based on the results of the practicality test on teachers it was categorized as very practical.